2001
DOI: 10.1080/713602922
|View full text |Cite
|
Sign up to set email alerts
|

Kallmann's syndrome: pregnancy through intracytoplasmic sperm injection and complicated by gestational diabetes

Abstract: Kallmann's syndrome is characterized by hypogonadotropic hypogonadism and anosmia. Assisted reproductive techniques such as intracytoplasmic sperm injection (ICSI) may be required to treat the infertile couple with oligozoospermia. Rare complications have been described in patients with Kallmann's syndrome, but gestational diabetes has not previously been reported. A case of Kallmann's syndrome with infertility is reported. Ovulation was successfully induced by human menopausal gonadotropin therapy, but pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Impaired semen quality prevented his spouse from conceiving and IVF helped the couple in having a healthy baby. Thereafter, some studies presented pregnancies achieved through IVF/ICSI in CHH patients not responding to hormonal treatment [ 9 , 10 ], and pregnancy rates from the large studies were 50–60% [ 11 , 12 ]. Gonadotropin replacement combined with TESE-ICSI cycles improved pregnancy rate of CHH patients [ 13 ], the clinical pregnancy rate was 17.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired semen quality prevented his spouse from conceiving and IVF helped the couple in having a healthy baby. Thereafter, some studies presented pregnancies achieved through IVF/ICSI in CHH patients not responding to hormonal treatment [ 9 , 10 ], and pregnancy rates from the large studies were 50–60% [ 11 , 12 ]. Gonadotropin replacement combined with TESE-ICSI cycles improved pregnancy rate of CHH patients [ 13 ], the clinical pregnancy rate was 17.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ovulation induction is essential for pregnancy in these cases. In the literature, a few deliveries have been reported for women with this syndrome undergoing ovulation induction by use of pulsatile GnRH [11], recombinant LH and FSH [12], hMG [13][14][15][16], and hMG then low-dose hCG [17].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that fertilization success is improved by ICSI for cases in which fertilization failure occurred in a previous IVF cycle [18]. Only 1 delivery by use of ICSI for a woman with Kallmann syndrome has been reported [14]. Another delivery was achieved by IUI [17].…”
Section: Discussionmentioning
confidence: 99%
“…Another recent report suggests diabetes may occur in patients with Kallmann's syndrome, but further investigation is required to establish whether gestational diabetes is associated with the syndrome or was coincidental in this case. 45…”
Section: Can Art Influence the Development Of Diabetes?mentioning
confidence: 99%